Algebra 2

posted by .

Choose the appropriate simplified expression.
1. 8x^2-10x+3/6x^2+3x-3


2. (x^2-4/x^2-1)*(x+1/x^2+2x)

3. (7/5y+25)-(4/3y+15)



4. (x^2/x^2+2x+1)/(3x/x^2-1)


5. (2x+4/3x-3)*(12x-12/x+5)

6. (7/2xy^2)+(3/8x^2y)


7. (x^2-16/2x+8)/((x-4)^2/8x-32)

8. 5-(4x^2-5x+1/x^2-x)

9. 1/3x/5/6y

  • Algebra 2 -

    Use Quadratic Formula.

    1. (x-3/4)(x-1/2) / (x-1/2)(x+1) =
    (x-3/4) / (x+1).

    2. (x+2)(x-2)/(x+1)(x-1) * (x+1)/x(x+2)= (x-2)/x(x+1).

    3. (7y/5+25) - (4y/3+15) =
    7y/5 + 25 - 4y/3 - 15 =
    Common denominator = 15.
    21y/15 + 25 - 20y/15 - 15 =
    y/15 + 10.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algbrea

    3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -28 = 2x -12 -28 =x -40 =x 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -10x+35=63 -10x=28 x=-2.8 you are both wrong! 3x - 15x + 35 = 2x + 18 + 45 …
  2. math

    Can someone please help me with these few problems here?
  3. Algebra

    almost done with Algebra...help! 2 3x – 6(2x – 0.055) = 10x + 0.515 I don't know what want but assuming your solving for x... 23x-12x-.33= 10x + 0.515 11x-.33= 10x + 0.515 x= 0.845 You need to clarify your post. Is that 23x or …
  4. Algebra

    simplify the following expression 10x - 12x
  5. Algebra

    I thought number 4 on this list was incorrect but didn't know how to fully explain it here is the list that I have. Please look at the following simplification of an algebraic expression. Which line contains the mistake and why?
  6. Algebra

    Please look at the following simplification of an algebraic expression. Which line contains the mistake and why?
  7. Algebra 1

    1) what is the simplified form of (x-2)(2x+3)?
  8. Algebra. Please check my answers

    Evaluate a/b+c^d for a=6,b=3,c=4 and d=5 A.42*** B.18 C.82 D.360 What is the simplified form of the expression ?
  9. 9th grade algebra (factoring with quadratic)

    Can you check the following problems? 4. x^2 - 10x +25 = 9 x^2 - 10x + (25 -9) = 9 - 9 x^2 - 10x + 16 = 0 (x - 8)(x-2) = 0 x - 8 = 0, x - 2 = 0 x = 8, x = 2 5. x^2 - 6x + 9 = 49 x^2 - 6x + ( 9 - 49) = 49 - 49 x^2 - 6x - 40 = 0 (x -10)(x
  10. 9th grade algebra (completing square)

    Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x

More Similar Questions